Perlindungan Hukum Keris Aeng Tong-Tong Sumenep Dalam Hukum Nasional dan Konvensi Internasional - Yenny Eta Widyanti (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2023)
Kris is an object of Indonesian culture which has beautiful artistic and high economic values. Kris making is still maintained in several areas, one of which is in Sumenep Regency. Since 2014, Sumenep Regency has been recognized by UNESCO as the area that has the most Mpu (makers of heirlooms) in the world and most of them are in Aeng Tong-Tong Village. The tradition of making kris in Sumenep has existed since the time of the Majapahit Kingdom and has continued to this day. The rapid development of the industry and the number of kris makers in Sumenep have made Sumenep the Indonesian Kris City. The aim of this research is to analyze the legal protection of the Aeng Tong-Tong Sumenep Kris based on national laws and international conventions using a statutory approach. The legal protection of the Aeng Tong-Tong Sumenep Kris in national law is contained in Law Number 28 of 2014 concerning Copyright and Law Number 5 of 2017 concerning the Promotion of Culture, while the legal protection of the Aeng Tong-Tong Sumenep Kris in International Conventions is contained in The Convention on the Protection and Promotion of the Diversity of Cultural Expressions 2005, The Convention for the Safeguarding of the Intangible Cultural Heritage 2003, and The Berne Convention for the Protection of Literary and Artistic Work. In realizing optimal legal protection for the Aeng Tong-Tong Sumenep Kris in national law and international conventions, a comprehensive legal protection must be provided including legal protection for Intellectual Property and Non-Intellectual Property. (Keris merupakan benda hasil budaya bangsa Indonesia yang memiliki nilai seni yang indah dan nilai ekonomi yang tinggi. Pembuatan keris tetap dipertahankan di beberapa daerah, salah satunya di Kabupaten Sumenep. Sejak Tahun 2014, Kabupaten Sumenep diakui oleh UNESCO sebagai daerah yang memiliki Mpu (pembuat benda pusaka) terbanyak di dunia dan sebagian besar ada di Desa Aeng Tong-Tong. Tradisi pembuatan keris di Sumenep sudah ada sejak zaman Kerajaan Majapahit dan masih terus bertahan hingga kini. Pesatnya perkembangan industri dan jumlah perajin keris di Sumenep menjadikan Sumenep sebagai Kota Keris Indonesia. Tujuan pada penelitian ini untuk menganalisis perlindungan hukum Keris Aeng Tong-Tong Sumenep berdasarkan hukum nasional dan konvensi internasional dengan menggunakan pendekatan perundangan. Perlindungan hukum Keris Aeng Tong-Tong Sumenep dalam hukum nasional terdapat dalam UU Nomor 28 Tahun 2014 tentang Hak Cipta dan UU Nomor 5 Tahun 2017 tentang Pemajuan Kebudayaan, sedangkan perlindungan hukum Keris Aeng Tong-Tong Sumenep dalam Konvensi Internasional terdapat dalam The Convention on the Protection and Promotion of the Diversity of Cultural Expression 2005, The Convention for the Safeguarding of the lntangible Cultural Heritage 2003, dan The Berne Convention for the Protection of Literary and Artistic Work. Dalam mewujudkan perlindungan hukum yang optimal terhadap Keris Aeng Tong-Tong Sumenep dalam hukum nasional dan konvensi internasional, maka harus dilakukan perlindungan hukum secara menyeluruh meliputi perlindungan hukum atas Kekayaan Intelektual dan Non Kekayaan Intelektual.)